PERHITUNGAN PENDAPATAN DAN BEBAN UNTUK MENGUKUR KINERJA KEUANGAN PERUSAHAAN JASA - Rahmadi, Adha; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to assess the financial performance of PT. Asuransi Jiwa Sequislife and the recognition ofpremium incomeandclaims expenseswithFinancial Accounting StandardsStatement (PSAK) No. 36. The result of this research shows that it has been found from the resultof analysis that the work plan and target from the sources of revenue, only the premium income has not fulfilled the target and the principle of income recognition which is basically compatible with Financial Accounting StandardsStatement (PSAK) No. 36, and the measurement of the revenue even though it cannot be explained in detail in the Financial Accounting Standards Statement (PSAK) No. 36 since it is considered as the general matters or things that are not regulated in the Financial Accounting StandardsStatement (PSAK) No. 36.Keywords: Financial Performance of Service Company, recognition of income and expenses, PSAK No. 36.